Analysis and Visualization of Advertising Sales Data Using Python Software Through an Internship Program - Ardiansyah, Muhammad Naufal; kalfin (International Journal of Mathematics, Statistics, and Computing, 2024)
This research discusses the use of data visualization as a tool for analyzing and presenting information effectively. The main goal of this research is visualization that allows better understanding of complex data. In this context, research explores various data visualization techniques, including the use of bar charts, correlation heatmaps, and interactive technology to present information intuitively. In improving decision-making abilities, identifying patterns or trends, and exploring relationships and insights contained in large and heterogeneous datasets. The research methodology includes comparative analysis of various visualization methods, user experiments, and the application of new techniques to evaluate the effectiveness and usefulness of data visualization in advertising video sales data at PT XXX. Based on the research results, it was found that data visualization involves presenting data information in graphic or image form to facilitate understanding. This helps in explaining the facts and determining the steps that need to be taken. The research results are expected to provide in-depth insight into the development of data visualization techniques. The results of this data visualization can be widely applied in various fields, especially creative, marketing and sales management.